Fluorescent nanodiamond – hyaluronate conjugates for target-specific molecular imaging - Han, Hye Hyeon (RSC Adv, 2021)
Despite wide investigation on molecular imaging contrast agents, there are still strong unmet medical needs to enhance their signal-to background ratio, brightness, photostability, and biocompatibility with multimodal imaging capability. Here, we assessed the feasibility of fluorescent nanodiamonds (FNDs) as carbon based photostable and biocompatible materials for molecular imaging applications. Because FNDs have negatively charged nitrogen vacancy (NV) centers, they can emit bright red light. FNDs were conjugated to hyaluronate (HA) for target-specific molecular imaging. HA is a biocompatible, biodegradable, and linear polysaccharide with abundant HA receptors in the liver, enabling liver targeted molecular imaging. In vitro cell viability tests revealed the biocompatibility of HA–FND conjugates and the competitive cellular uptake test confirmed their target-specific intracellular delivery to HepG2 cells with HA receptors. In addition, in vivo fluorescence lifetime (FLT) assessment revealed the imaging capability of FNDs and HA–FND conjugates. After that, we could confirm the statistically significant liver-targeted delivery of HA–FND conjugates by in vivo imaging system (IVIS) analysis and ex vivo biodistribution tests in various organs. The renal clearance test and histological analysis corroborated the in vivo biocompatibility and safety of HA–FND conjugates. All these results demonstrated the feasibility of HA–FND conjugates for further molecular imaging applications.